Clinical outcomes of surgical clipping for intracranial aneurysms in patients with a Hunt and Hess grade 4 or 5 - Zhang,Yang (2016)
ABSTRACT We retrospectively evaluated the records of 49 grade 4 and 5 patients with 42 intracranial aneurysms treated within 72 h of subarachnoid hemorrhage (SAH). In total, 35 patients (71%) were grade 4, and 14 (29%) were grade 5. A total of 42 (85%) patients had one aneurysm, 6 (12%) had two aneurysms, and 1 (3%) had three aneurysms. Out of 49 patients, one technical (2%) and one clinical (2%) complication occurred at surgery. Twenty-one (43%) patients recovered well, including 7 with postoperative hematoma requiring an immediate evacuation of a clot. Fourteen (29%) patients had hydrocephalus and required a ventriculo-peritoneal shunt; 12 patients underwent tracheotomy postoperatively due to coma and pulmonary infection. We found that patients with Hunt and Hess grade 4 and 5 aneurysms can undergo successful neurosurgical clipping of the aneurysms after SAH. However, the morbidity and mortality rates remain high because of their poor clinical condition and a high incidence of vasospasm during treatment.